2017
DOI: 10.1016/j.soildyn.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Seismic microzoning of Štip in Macedonia

Abstract: Keywords:Microzonation maps, which include descriptions of site geology and site soil properties Contribution of a large distant earthquake to the design strong motion amplitudes Computation of seismic hazard for earthquake sources, which follow different attenuation laws A B S T R A C T Seismic microzonation maps for Štip (Macedonia) and its surroundings are presented based on the uniformhazard-spectrum (UHS) methodology. Such mapping satisfies the guidelines for performance-based design (PBD), which requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Expectations of all UHS amplitudes will then have the same probability of exceedance in t years. Several recent studies of seismic microzonation in the region of north-western Balkans [25][26][27][28][29][30], which considered frequency-dependent attenuation equations and took also into account the deep geology effects, have confirmed the merits of the UHS approach. The comparison between the UHS-based and standard seismic microzonation studies is presented in Figure 3.…”
Section: Citymentioning
confidence: 81%
See 1 more Smart Citation
“…Expectations of all UHS amplitudes will then have the same probability of exceedance in t years. Several recent studies of seismic microzonation in the region of north-western Balkans [25][26][27][28][29][30], which considered frequency-dependent attenuation equations and took also into account the deep geology effects, have confirmed the merits of the UHS approach. The comparison between the UHS-based and standard seismic microzonation studies is presented in Figure 3.…”
Section: Citymentioning
confidence: 81%
“…However, several regional seismic microzonation and strong ground motion studies [24][25][26][27][28][29][30] have shown that the deep geology, i.e., the geological characteristics up to depths of hundreds of meters or even a few kilometers [31], strongly influence seismic waves with both the shorter and longer oscillation periods. These studies show that even if the shallow geology description takes into account more than 30 m of the local soil depth (e.g., in the case we use the Seed's et al [32] classification), empirical predictions may still be biased, so the deeper geology conditions need to be considered.…”
Section: Citymentioning
confidence: 99%
“…Several recent studies have shown that such local soil and groundwater features may significantly affect the severity of the surface ground motion during strong earthquakes [10][11][12][13]. Seismic microzonation studies in the north-western Balkans [14][15][16][17][18] and a recent study of strong earthquake ground motion in the same region [19] have also shown that deep geological sediments strongly affect the severity of both longer and shorter wave periods. The same studies have shown that in areas with moderate local seismicity but with deep geological sediments, the severity of longer wave periods can be significant during more distant earthquakes.…”
Section: Seismic Exposurementioning
confidence: 99%
“…Microzoning maps were first introduced to depict detailed spatial variation in the amplitudes of earthquake shaking due to variations in the site geology 1–4 . It was later recognized that significant additional variation in ground motion is also caused by local soils 5–9 . Thus, it is necessary that both the site soil and site geology are included in the empirical scaling equations of strong ground motion amplitudes 10–13 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It was later recognized that significant additional variation in ground motion is also caused by local soils. [5][6][7][8][9] Thus, it is necessary that both the site soil and site geology are included in the empirical scaling equations of strong ground motion amplitudes. [10][11][12][13] In addition, significant spatial variation in seismic hazard is also expected from spatial heterogeneity in the seismicity over various seismic sources and the frequency-dependent attenuation of strong motion amplitudes along the source to the site path.…”
Section: Introductionmentioning
confidence: 99%